MND1 and PSMC3IP control PARP inhibitor sensitivity in mitotic cells - Zelceski, Anabel; Francica, Paola; Lingg, Lea; Mutlu, Merve; Stok, Colin; Liptay, Martin; Alexander, John; Baxter, Joseph S.; Brough, Rachel; Gulati, Aditi; Haider, Syed; Raghunandan, Maya; et al. (Cell reports (Cambridge), 2023)
The PSMC3IP-MND1 heterodimer promotes meiotic D loop formation before DNA strand exchange. In genome-scale CRISPR-Cas9 mutagenesis and interference screens in mitotic cells, depletion of PSMC3IP or MND1 causes sensitivity to poly (ADP-Ribose) polymerase inhibitors (PARPi) used in cancer treatment. PSMC3IP or MND1 depletion also causes ionizing radiation sensitivity. These effects are independent of PSMC3IP/MND1’s role in mitotic alternative lengthening of telomeres. PSMC3IP- or MND1-depleted cells accumulate toxic RAD51 foci in response to DNA damage, show impaired homology-directed DNA repair, and become PARPi sensitive, even in cells lacking both BRCA1 and TP53BP1. Epistasis between PSMC3IP-MND1 and BRCA1/BRCA2 defects suggest that abrogated D loop formation is the cause of PARPi sensitivity. Wild-type PSMC3IP reverses PARPi sensitivity, whereas a PSMC3IP p.Glu201del mutant associated with D loop defects and ovarian dysgenesis does not. These observations suggest that meiotic proteins such as MND1 and PSMC3IP have a greater role in mitotic DNA repair. [Display omitted] •The PSMC3IP-MND1 heterodimer controls meiotic DNA recombination•PSMC3IP-MND1 controls mitotic recombination•PSMC3IP-MND1 loss causes PARPi sensitivity genes in mitotic cells•PSMC3IP-MND1 loss causes a D loop defect and toxic RAD51 Processes used by meiotic cells to recombine chromosomes are also often co-opted in mitotic DNA repair. Zelceski et al. show that the meiotic PSMC3IP-MND1 heterodimer plays a critical role in the response to DNA damage in mitotic cells, including the response to PARPi used in cancer treatment.